Carbon Deposition Diagnostics for Reliability and State-of-Health Assessment of SOFC. (10th April 2018) - Ploner, Alexandra; Hagen, Anke; Hauch, Anne
Abstract : Operation of Solid Oxide Fuel Cells (SOFCs) with carbon-based fuels is a major advantage of this specific fuel cell technology. Yet, the use of carbon-containing fuels can lead to deactivation of the cell if carbon deposition occurs. Therefore, this study simulates failure on a Ni-YSZ-supported cell under steam reforming conditions by stopping the steam supply and investigates the cell voltage and temperature responses due to this fault. Simultaneously, time-dependent electrochemical impedance spectroscopy (EIS) monitoring during cell operation was performed which could be correlated to two processes, one mainly originating from support layer and another from the active anode layer of the cell in a Ni-YSZ supported cell. Monitoring via EIS may therefore be used to allow recognition of carbon deposition in due course and give the opportunity to counteract before detrimental failure occurs.